High Accuracy for Mixes Finite Element Methods in Raviart-Thomas Element (Journal of Computational Mathematics, 1996)
This paper deals with Raviart-Thomas element ($Q_{2,1}× Q_{1,2}-Q_1$ element). Apart from its global superconvergence property of fourth order, we prove that a postprocessed extrapolation can globally increased the accuracy by fifth order.